HUBUNGAN BALANCED SCORECARD DENGAN KINERJA PERUSAHAAN BESERTA BEBERAPA FAKTOR YANG MEMPENGARUHI - Etty Murwaningsari Nasser; Zulfitry Ramdan (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2009)
The objective of this research is to examine the relation between several factors which influence balance scorecard (e.g. organization Size, Product Life Cycle, Market Position) and balance scorecard. The further investigation is to examine the relation between balance scorecard and performance with organization Size, Product Life Cycle, and Market Position as moderating variable. The research examined 20 manufacturing companies in 2007. The primary data were collected by questionairre, and the number of respondent are 20 monetary manager of manufacturing business consist of organizational size, product life cycle, market position and the usage of four perspective of balanced scorecard. Statistical test is using multiple regression and moderated regression analysis. The empirical result of this research shows that First, only market position which has significant influence to the usage of balanced scorecard. Second, the usage of balanced scorecard does not benefit for large organization to increase Organizational Performance. Third, the usage of balanced scorecard does not benefit for organization in introduction stage to increase Organizational Performance. And Finally, the usage of Balanced scorecard does not benefit for organization with strong market position to increase Organizational Performance